Reproduction of Eisenia foetida in agricultural soils from mining areas contaminated with copper and arsenic - Ávila, Gonzalo; Gaete, Hernán; Morales, Mario; Neaman, Alexander (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate copper and arsenic toxicity in agricultural soils, by means of standardized bioassays of chronic and acute toxicity on Eisenia foetida, and to relate E. foetida response to copper and arsenic concentrations in soils. The agricultural soils were sampled in the proximity of copper mining industries, in the Aconcagua river basin, Chile. E. foetida exposed to the studied soils exhibited a low mortality, indicating the absence of acute toxicity. Besides, a decrease in the cocoon production and juvenile development was observed, indicating the existence of chronic toxicity. Reduction in the cocoon production and juvenile development was related to soil concentrations of copper and arsenic. Both copper and arsenic reduced the cocoon production, while only arsenic diminished the juvenile development. Agricultural soils from mining areas of the basin have potentially toxic characteristics for the development of soil macrofauna.